Informal Caregiver Burden in Middle-income Countries: Results from Memory Centers in Lima – Peru - Custodio, Nilton (2014)
Objective: The aim of this study was to evaluate caregiver burden based on Zarit Burden Interview (ZBI) and depression in caregivers on the Beck Depression Inventory-II (BDI-II). Methods: Literate individuals, 18 years or older, who spoke Spanish as their native language were included. Demographic characteristics: Age, sex, education, relationship to person with dementia, length of time caregiving, other sources of help for caring, impact on the household economy, family support, and perception of impaired health; and Clinical data on care-recipients: type of dementia, time since diagnosis, treatment, and Global Deterioration Scale (GDS); the ZBI and BDI-II. Descriptive and analytical statistics were employed to assess caregiver burden and predictors of higher burden in caregivers. Results: A total of 92 informal caregivers were evaluated. Regarding care-recipients, 75% were 69 years old or over, 75% had at least one year since diagnosis, 73.9% had Alzheimer’s disease, 84.8% received treatment, 75% scored 5 or over on the GDS. For caregivers, 75% were 55.5 years old or over, predominantly female (81.5%), married (83.7%), the spouse of care-recipients (60.87%), had at least 10 years of education (75.0%) and one year of caregiving (75%), reduced entertainment time (90.2%) and self-perception of impaired health (83.7%). Median score on the ZBI was 37.5 (minimum value = 3; and maximum value = 74). The coefficient of BDI was 1.38 (p-value <0.001). Conclusion: This sample of Peruvian informal caregivers showed elevated ZBI values. Self-perception of worsened health, repercussion on the family economy and time caregiving were the main determinants of ZBI, although only BDI was a consistent predictor of ZBI.